Data-Driven, Web-Based Parameter Identification for a Reduced-Order Model of the Chilean Power System - Chavez-Orostica, H; Quiroz-Moreno, J; Gonzalez-Pincheira, L (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The current need for power-system control-room operational tools to increase real-time situational awareness has led to various proposals on data analytics algorithms to obtain operational information from SCADA and PMU power system networks. Most of the proposals are implemented in simulation, with reduced practical significance for system operators. This work proposes a web-based simple algorithm to identify the dynamic parameters of a reduced-order model of power system frequency dynamics that is implemented with industrial hardware on a PMU network in the Chilean power system. To demonstrate the applicability of the proposed tool, the algorithm is implemented in a web page with real-time monitoring of the frequency of the Chilean power system, so that utilities and academic institutions with access to PMU measurements can apply the proposed concepts regardless of the topology of the monitored system. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.